The personal is still political : Sexual orientation, gender identity and the politics of law making in Africa - Dinokopila, Bonolo; Kaime, Thoko (Intractable Problems of Human Rights, 2025)
This chapter critically examines the politicisation of sexual orientation and gender identity (SOGIE) rights in Africa. It highlights how anachronistic, colonial-era sodomy laws have evolved into a second wave of harsh anti-homosexuality legislation. Despite growing international recognition of SOGIE rights as fundamental human rights, many African states have intensified efforts to criminalise queerness under the guise of protecting morality, family values, and national identity. The chapter analyses the legal, political and sociocultural dynamics that sustain this trend, with a particular focus on Uganda, Nigeria and Ghana, whose laws serve as case studies of widespread legalised repression. These laws not only criminalise samesex acts and relationships but also ban advocacy, restrict freedom of association, and impose surveillance obligations on citizens. The proliferation of such laws is rooted in a complex interplay of factors, including colonial legacies, religious fundamentalism, and the instrumentalisation of queerness as a symbol of resistance to Western influence. The chapter also addresses the role of institutions such as the church and state in perpetuating discrimination and violence, often with impunity. It contrasts these regressive trends with progressive developments in jurisdictions such as Namibia, South Africa and Botswana, where courts have moved to protect SOGIE rights despite significant push-back. Drawing from feminist theory – particularly the notion that ‘the personal is political’ – the chapter reframes the oppression of queer Africans as a political crisis rather than a private issue of morality. It concludes by advocating collective action and regional solidarity to challenge the legal and cultural systems that dehumanise queer identities. By doing so, the chapter situates SOGIE rights within the broader fight for human dignity, equality and decolonisation in Africa, insisting that meaningful change requires confronting the political roots of exclusion and affirming the humanity of all individuals, regardless of their identity.